2014
DOI: 10.1099/ijs.0.058115-0
|View full text |Cite
|
Sign up to set email alerts
|

Oceanisphaera profunda sp. nov., a marine bacterium isolated from deep-sea sediment, and emended description of the genus Oceanisphaera

Abstract: Oceanisphaera profunda sp. nov., a marine bacterium isolated from deep-sea sediment, and emended description of the genus Oceanisphaera A Gram-stain-negative, aerobic, oxidase-and catalase-positive, flagellated, rod-shaped bacterial strain, designated SM1222 T , was isolated from the deep-sea sediment of the South China Sea.The strain grew at 4-35 6C and with 0.5-8 % NaCl (w/v). Phylogenetic analysis based on the 16S rRNA gene sequences revealed that strain SM1222 T was affiliated with the genus Oceanisphaera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The genus Oceanisphaera was first described by Romanenko et al (2003) with Oceanisphaera litoralis as the type species. At the time of writing, the genus Oceanisphaera is comprised of six recognized species ( http://www.bacterio.net/m/oceanisphaera.html ): O. litoralis (Romanenko et al , 2003), Oceanisphaera donghaensis (Park et al , 2006), Oceanisphaera ostreae (Choi et al , 2011), Oceanisphaera sediminis (Shin et al , 2012), Oceanisphaera arctica (Srinivas et al , 2012) and Oceanisphaera profunda (Xu et al , 2014). Members of the genus are aerobic, psychrotolerant and moderately halophilic.…”
mentioning
confidence: 99%
“…The genus Oceanisphaera was first described by Romanenko et al (2003) with Oceanisphaera litoralis as the type species. At the time of writing, the genus Oceanisphaera is comprised of six recognized species ( http://www.bacterio.net/m/oceanisphaera.html ): O. litoralis (Romanenko et al , 2003), Oceanisphaera donghaensis (Park et al , 2006), Oceanisphaera ostreae (Choi et al , 2011), Oceanisphaera sediminis (Shin et al , 2012), Oceanisphaera arctica (Srinivas et al , 2012) and Oceanisphaera profunda (Xu et al , 2014). Members of the genus are aerobic, psychrotolerant and moderately halophilic.…”
mentioning
confidence: 99%
“…Beta diversity analyses showed that the microbiomes of all external body sites were similar to those of the surrounding environment, and there were fewer statistically significant differences between the environmental samples and external body sites compared to internal body sites. Similarly, both environmental and external penguin samples were primarily dominated by the same phyla, including the bacterial genera Oceanisphaera and Psychrobacter, which have been associated with both planktonic 34 , 35 and host-associated marine microbiomes 36 , 37 . Together, these trends suggest that the external African penguin microbiome is strongly influenced, and likely influences, the microbiome of immediate surrounding environment, with transfer of microbes likely routinely occurring between these body sites and the water and various surfaces of the managed care exhibit.…”
Section: Discussionmentioning
confidence: 99%